Exposure to brominated and organophosphate ester flame retardants in U.S. childcare environments: Effect of removal of flame-retarded nap mats on indoor levels. (July 2018) - Stubbings, W.A.; Schreder, E.D.; Thomas, M.B.; Romanak, K.; Venier, M.; Salamova, A.
Abstract: We assessed exposure to 39 brominated and 16 organophosphate ester flame retardants (FRs) from both dust and indoor air at seven childcare centres in Seattle, USA, and investigated the importance of nap mats as a source of these chemicals. Many childcare centres serving young children use polyurethane foam mats for the children's naptime. Until recently, the vast majority of these mats sold in the United States contained flame-retarded polyurethane foam to meet California Technical Bulletin 117 (TB117) requirements. With the 2013 update of TB117, allowing manufacturers to meet flammability standards without adding FRs to filling materials, FR-free nap mats have become widely available. We conducted an intervention study by actively switching out FR-treated nap mats with FR-free nap mats and measuring FR levels in indoor air and dust before and after the switch-out. The predominant FRs found in dust and indoor air were 2-ethylhexyl tetrabromobenzoate (EHTBB) and tris (1-chloro-2-propyl) phosphate (TCIPP), respectively. Nap mat samples analysed from four of the six centres contained a Firemaster ® mixture, while one mat was predominantly treated with tris (1, 3-dichloroisopropyl) phosphate (TDCIPP) and the other contained no detectable target FRs. After replacement, there was a significant decrease ( p  = 0.03–0.09) in median dust concentrations for bis (2-ethylhexyl) tetrabromophthalate (BEHTBP), EHTBB, tris (4-butylphenyl) phosphate (TBPP), and TDCIPP with reductions of 90%, 79%, 65%, and 42%, respectively. These findings suggest that the nap mats were an important source of these FRs to dust in the investigated childcare environments and that a campaign of swapping out flame-retarded mats for FR-free ones would reduce exposure to these chemicals. While calculated exposure estimates to the investigated FRs via inhalation, dust ingestion, and dermal absorption were below established reference dose values, they are likely underestimated when considering the toddlers' direct contact to the mats and personal cloud effects. Graphical abstract: Image 1 Highlights: Occurrence of BFRs and OPEs was assessed in dust and indoor air in Seattle childcare centers. Nap mats were investigated as an important source of these chemicals. Swapping to FR-free nap mats resulted in significant reduction in the levels of several FRs. Abstract : An intervention focused on swapping nap mats containing flame retardants with nap mats free of flame retardants in Seattle childcare centres resulted in significant reduction of several of these chemicals in indoor dust, suggesting that nap mats were an important source of these chemicals.